Trait associations in common bean genotypes grown under drought stress and field infestation by BSM bean fly - Ambachew, Daniel; Mekbib, Firew; Asfaw, A.; Beebe, Stephen E.; Blair, Matthew W. (Elsevier, 2015)
Understanding functional relations among plant traits and their modulation by growing conditions is imperative in designing selection strategies for breeding programs. This study assessed trait relationships among 196 common bean genotypes exposed to stresses for drought and field infestation of bean fly or bean stem maggot (BSM). The study was carried out at two locations and data was analyzed with linear correlation, path coefficient and genotype × trait biplot analyses. Multiple trait data related to mechanisms of drought and bean fly tolerance were collected on 196 genotypes grown under i) water deficit at mid-pod fill, or ii) unprotected against bean fly; iii) irrigated, well watered conditions, or iv) bean fly protection with chemicals. Seed yield exhibited positive and significant correlations with leaf chlorophyll content, vertical root pulling resistance, pod harvest index, pods per plant and seeds per pod at both phenotypic and genotypic levels under stress and non-stress conditions. Genotypic correlations of traits with seed yield were greater than their respective phenotypic correlations across environments indicating the greater contribution of genotypic factors to the trait correlation. Pods per plant and seeds per pod had high positive direct effects on seed yield both under stress and non-stress whereas pods per plant had the highest indirect effect on seed yield through pod harvest index under stress. In general, our results suggest that vertical root pulling resistance and pod harvest index are important selection objectives for improving seed yield in common beans under non-stress and stress conditions, and particularly useful for drought and BSM tolerance evaluation.